Unveiling Gender Resistance in the Discourse of Sinf-e-Ahan Title Track: A Study of Empowering Strength and Dismantling of Gender Stereotypes in Pakistani Society - Maham Noor; Nimra Saud; Irsa Shafique (Indus Journal of Social Sciences, 2025)
Using an analysis of the lyrics of the Sinf-e-Aahan title track, this study investigates the representation of the idea of resistance of gender in the modern Pakistan society where the empowerment, strength and abandonment of gender norms is highlighted in the lyrics. Through critical analysis of the major lines of the lyrics, the study reveals how the song disrupts patriarchal views and makes the Pakistani woman iconic of self-determination and resilience. The title track is not just a cultural artifact itself but a strong one, speaking feminist agenda and calling for female liberation in a male-ruled society. This study, based on Pakistan’s socio-political and cultural context, using feminist critical discourse theory, and taking a qualitative methodological approach, examines on the deliberate choice of language that resisted conventional gender expectations. The research explains the importance of lyrics which act as a strong tool for promoting feminism and the denial of dominant cultural norms. Exemplifying the potentials of popular music in producing positive gender narrations, this study contributes to academic debates on female representation in South Asian media.